Characteristic patterns of microRNA expression in human bladder cancer - Zabolotneva, Anastasia A.; Zhavoronkov, Alex; Garazha, Andrew V.; Roumiantsev, Sergey A.; Buzdin, Anton A. (Frontiers in Genetics, 2013)
MicroRNAs (miRNAs) are small, noncoding RNAs that post-transcriptionally regulate gene expression. Their altered expression and functional activity have been observed in many human cancers. MiRNAs represent promising diagnostic and prognostic molecular biomarkers, and also serve as novel therapeutic targets. We performed a systematic analysis of scientific reports that link differences in miRNA expression with the pathogenesis of bladder cancer. This literature review is the first comprehensive database of miRNA molecules with biased expression profiles in bladder cancer. Among the 95 differentially expressed miRNAs that we identified from the literature, we classify 48 as upregulated in bladder cancer, 35 as downregulated, and 12 as contradictory (contradictory data were reported in one or more studies on the gene). In addition, we discuss the possible roles of differentially expressed miRNAs in the regulation of intracellular signaling pathways in bladder cancer.